Identification and editing of stem-like cells in methylcholanthrene-induced sarcomas. (2nd January 2019) - Gross, Emilie T. E.; Peinado, Carlos D.; Jung, Yujin; Han, Semi; Liu, Beichen; Santosa, Endi K.; Bui, Jack D.
ABSTRACT: The cancer stem cell (CSC) paradigm posits that specific cells within a tumor, so-called CSC-like cells, have differing levels of tumorigenicity and chemoresistance. Original studies of CSCs identified them in human cancers and utilized mouse xenograft models to define the cancer initiating properties of these cells, thereby hampering the understanding of how immunity could affect CSCs. Indeed, few studies have characterized CSCs in the context of cancer immunoediting, and it is currently not clear how immunity could impact on the levels or stem-like behavior of CSCs. Using the well-studied 3′methylcholanthrene (MCA) model of primary sarcoma formation, we have defined a CSC-like population within MCA-induced sarcomas as expressing high levels of stem cell antigen-1 (Sca-1) and low levels of CD90. These Sca-1 + CD90 − CSC-like cells had higher tumor initiating ability, could spontaneously give rise to Sca-1-negative cells, and formed more sarcospheres than corresponding non-CSC-like cells. Moreover, when examining MCA-induced sarcomas that were in the equilibrium phase of cancer growth, higher levels of CSC-like cells were found compared to MCA-induced sarcomas in the escape phase of cancer progression. Notably, CSC-like cells also emerged during escape from anti-PD-1 or anti-CTLA4 therapy, thus suggesting that CSC-like cells could evade immune therapy. Finally, we demonstrate that paradoxically, interferon (IFN)-γ produced in vivo by immune cells could promote the emergence of CSC-like cells. Our findings define the existence of a Sca1 + CD90 − CSC-like population in the MCA-sarcoma model capable of differentiation, tumorsphere formation, and increased tumor initiation in vivo . These cells may also act as mediators of immune resistance during cancer immunoediting and immune therapy.